miR-423-3p inhibits CTNNBIP1/WNT preventing hyperandrogenic polycystic ovary syndrome - Zhang, Shanshan; Liu, Yajing; Wang, Mingming; Ponikwicka-Tyszko, Donata; Wolczynski, Slawomir; Chen, Li; Huang, Xuan; Yao, Bing; Rahman, Nafis A.; Li, Xiangdong (Oxford University Press (OUP), 2026)
Polycystic ovary syndrome (PCOS) lacks the generally accepted diagnostic biomarkers and targeted therapy. Increasing evidence indicates that microRNAs play a crucial role in PCOS. Hereby, we tested the functional implications of a novel MicroRNA (miR-423-3p) as a mediator in the progress of hyperandrogenic PCOS, as well as its potential as a new serum biomarker and therapeutic target for the PCOS. We found significantly decreased miR-423-3p levels in serum, human granulosa cells (hGCs), and follicular fluid of PCOS patients (n = 40) compared to healthy controls (n = 30), and this decrease corroborated in PCOS-like mouse models. The receiver operating characteristic curve analysis for circulating miR-423-3p indicated high diagnostic potential as a biomarker, with an area under the curve of 82%. miR-423-3p influenced hGC (Human ovarian granulosa cell line KGN) proliferation by directly targeting CTNNBIP1-modulated Wingless-type (WNT) signaling pathway. We further proved as mechanistic role that the elevated dihydrotestosterone inhibited the expression of miR-423-3p via the activation of the androgen receptor, and the overexpression of miR-423-3p normalized the function of androgen-induced GCs. While we overexpressed miR-423-3p, it counteracted androgen-induced dysfunction in GCs. Antiandrogen treatment restored the reproductive phenotypes in letrozole-induced PCOS-like mice and regulated miR-423-3p expression and its downstream effects. Ovarian intrabursal injection of miR-423-3p antagomir in wild-type mice induced PCOS-like phenotypes, further underscoring its functional role. Our results demonstrated that miR-423-3p emerged as a novel mediator in hyperandrogenic PCOS progression, and it holds promise as both a diagnostic biomarker and a therapeutic target.Sentence miR-423-3p may play a novel role in hyperandrogen polycystic ovary syndrome (PCOS) progression, serving as a potential serum biomarker and therapeutic target. It helps prevent hyperandrogenic PCOS by inhibiting the CTNNBIP1/WNT signaling pathway.